PRESERVATION AND VALUES OF SAPE SONOK'S PERFORMING ART TRADITION AS A CREATIVE CULTURE INDUSTRY - Jamilatul Hasana; Suryo Tri Saksono (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2022)
"Sape Sonok" Tradition rely on obedience, the aesthetics of the cow in walking, climbing wooden steps, and discipline. The purpose of this study is to find out how the Madurese people interpret Sape Sonok as part of their life and its relationship with the tourism industry. In order to answer these questions, this study will be carried out by applying ethnographic methods, especially Developmental Research Sequence (Spradley, 1997: 57). The use of this method is based on considerations that will be studied are cultural issues, especially traditional arts, in relation to the tourism industry. This study is included in qualitative research. Sape Sonok is a performing art that has been going on for decades. Sape Sonok cultural tourism can be applied starting from the Sape Sonok village to the landmark “image of the Madura region through the Sonok cattle performing arts tour package, which offers a variety of performing arts and creative economy.